Demographic and Health Status Differences Among People Aged 45 or Older With and Without Functional Difficulties Related to Increased Confusion or Memory Loss, 2011 Behavioral Risk Factor Surveillance System - Anderson, Lynda A. (Prev Chronic Dis, 2015)
We examined the demographic and health characteristics of people aged 45 years or older in 21 states with self-reported increased confusion or memory loss (ICML) (n = 10,583) by whether or not they also reported functional difficulties related to ICML. We used data from the 2011 Behavioral Risk Factor Surveillance System optional module on impact of cognitive impairment. After adjusting for demographic differences, we found that respondents with ICML and functional difficulties were significantly more likely than those with ICML and no functional difficulties to report frequent poor physical health, frequent poor mental health, limited activity due to poor physical or mental health, and a need for more help. Further understanding of the implications for long-term services and supports is needed.